How to Read and Calculate Diameter Size from Electron Microscopy Images - Yustika Desti Yolanda; Asep Bayu Dani Nandiyanto (ASEAN Journal of Science and Engineering Education, 2022)
Scanning electron microscopy (SEM) and Transmission Electron Microscopy (TEM) is a chemical instrument that can be used to evaluate the characteristics of material. Techniques can be used to determine the morphology and diameter size of material. However, until now there has been no publications that describes in detail to read and interpret the electron microscopy images of both SEM and TEM. The purpose of this paper is to demonstrate the steps how to read and calculate the electron microscopy images based on the level of difficulties: (1) simple shape, (2) fairly complex shape, (3) very complex shape. This paper has the potential to be used as standard information of how to read and calculate diameter size of material from Electron Microscopy Images.